Antiviral peptides against SARS-CoV-2: therapeutic targets, mechanistic antiviral activity, and efficient delivery - Raahilah, Zahir Essa; Wu, Yuan Seng *; Kalaivani, Batumalaie; Mahendran, Sekar; Poh, Chit Laa * (Springer, 2022)
The global pandemic of COVID-19 is a serious public health concern. Over 625 million confirmed cases and more than 6 million deaths have been recorded worldwide. Although several vaccines and antiviral medications have been developed, their efficacy is limited by the emerging new SARS-CoV-2 strains. Peptide-based therapeutics is a fast-growing class of new drugs and have unique advantages over large proteins and small molecules. Antiviral peptides (AVPs) are short polycationic antivirals with broad-spectrum effects, which have been shown to exert both prophylactic and therapeutic actions against reported coronaviruses. The potential therapeutic targets of AVPs are located either on the virus (e.g., E-protein and S-protein) to prohibit viral binding or host cells, particularly, those present on the cell surface (e.g., ACE2 and TMPRSS2). Despite AVPs having promising antiviral effects, their efficacy is limited by low bioavailability. Thus, nanoformulation is a prerequisite for prolonged bioavailability and efficient delivery. This review aimed to present an insight into the therapeutic AVP targets on both virus and host cells by discussing their antiviral activities and associated molecular mechanisms. Besides, it described the technique for discovering and developing possible AVPs based on their targets, as well as the significance of using nanotechnology for their efficient delivery against SARS-CoV-2.